2006
DOI: 10.2139/ssrn.950265
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and Bank Behavior

Abstract: This paper explores how the legal environment affects bank behavior in 20 transition economies. Based on a newly constructed data set we find that banks' loan portfolio composition depends on the legal environment. If banks operate in a well-functioning legal environment they lend relatively more to SMEs and provide more mortgages.On the other hand, banks lend more to large enterprises and to the government if the legal system is unsound. As a transmission channel we identify the banks' willingness to accept c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Therefore, this effect is expected to play a greater role for borrowers when the degree of information asymmetries is higher from the bank's perspective. As observed by Haselmann and Wachtel (2006), these asymmetries should be weaker when banks lend money to government entities than to other borrowers as the ability of the government to tax means a lower default risk, which, in turn, leads to lower requirements for the bank to gather information. Thus, we expect a weaker detrimental effect of corruption on bank lending to government entities.…”
Section: V3 Estimations By Category Of Loansmentioning
confidence: 97%
“…Therefore, this effect is expected to play a greater role for borrowers when the degree of information asymmetries is higher from the bank's perspective. As observed by Haselmann and Wachtel (2006), these asymmetries should be weaker when banks lend money to government entities than to other borrowers as the ability of the government to tax means a lower default risk, which, in turn, leads to lower requirements for the bank to gather information. Thus, we expect a weaker detrimental effect of corruption on bank lending to government entities.…”
Section: V3 Estimations By Category Of Loansmentioning
confidence: 97%
“…Most of these family businesses are highly successful ( The Economist , 1996) and they cannot be judged by the transactional lending practices. Marisetty et al ’s (2008) study finds that, in case of family business, the successor becomes the owner of the business, and the performance of the company depends on this family relationship. Hence, along with transaction lending, relationship lending should be considered in the framework for MSME financing for markets like India.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An important part of literature has confirmed that bank lending activities are influenced by the institutional landscape (Haselmann & Wachtel, 2006; Lepetit, Nys, Rous, & Tarazi, 2008). With bad institutional quality, and generally marked by government instability, high levels of corruption and weak legal protection of creditors, the level of NPLs increases and banks are highly exposed to default risk (Lambsdorff & Teksoz, 2004).…”
Section: Introductionmentioning
confidence: 99%